Problematika Pembelajaran Tematik Terpadu di Min III Bondowoso - MUHITH, ABD (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
This study aims to describe and analyze the problematic of integrated thematic learning in Madrasah Ibtidaiyah Negeri III Bondowoso. This research uses qualitative approach, case study type. Data collection techniques used in-depth interviews, participant observation and documentation study. The collected data is interpreted and analyzed using data reduction process, data presentation and conclusion. The validity of the data is checked by credibility test through extension of engagement and observation; triangulation; member checks, and conduct peer examination, dependability, confirmability, and transferability. Conclusion of this research: 1) Problem planning is: a) teacher still adopt RPP which become reference of learning: b) less critical in doing adaptation; c) lack of accuracy in elaborating operational verbs on basic competencies to be Indicators; and e) lesson planning done less in accordance with scientific theory. 2) The problem of learning implementation are: a) Teachers are less professional; b) Teachers difficulty in providing an integrated understanding of students; c) Teachers have difficulty converting subjects; d) Teachers difficult to integrate maple; e) Unavailability of adequate learning facilities; and e) Students cannot understand the implementation of integrative thematic learning. 3) the problem of integrative thematic assessment is: a) the teacher difficulties assessing each maple on the report card about the students' attitudes; b) practically the conduct of the assessment is not in accordance with the principle of assessment that should be done in integrative thematic learning activities; c) in general teachers can carry out an authentic assessment; and 4) The strategies that will be used to streamline integrative thematic learning activities are by: a) improving teachers' human resources through training activities; b) pursuing educational channels appropriate to their field; c) hold regular meetings of coordination meetings between KKM conducted every 3 months; and d) on improving aspects of learning tools by supplementing the latest literature reading books in order for students to have additional knowledge.